2020
DOI: 10.1093/jas/skaa270
|View full text |Cite
|
Sign up to set email alerts
|

Increase of E3 ubiquitin ligase NEDD4 expression leads to degradation of its target proteins PTEN/IGF1R during the formation of goose fatty liver

Abstract: Goose fatty liver may have a unique protective mechanism as it does not show a pathological injury even in the case of severe steatosis. Although NEDD4 participates in repair and regeneration of injured liver through its target proteins, its role in nonalcoholic fatty liver disease (NAFLD) remains unknown. Using qPCR and immunoblot analyses, here we found that the mRNA and protein expressions of NEDD4 were induced in goose fatty liver, compared to normal liver. The mRNA expression of PTEN and IGF1R was also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The seed node of module 2 is FBXO30 , which acts as an ubiquitin ligase. A recent study indicated that expression of protein ubiquitination in goose fatty liver was higher than in the normal liver ( Yan et al, 2020 ). This result appears to support other results regarding fatty liver development.…”
Section: Discussionmentioning
confidence: 99%
“…The seed node of module 2 is FBXO30 , which acts as an ubiquitin ligase. A recent study indicated that expression of protein ubiquitination in goose fatty liver was higher than in the normal liver ( Yan et al, 2020 ). This result appears to support other results regarding fatty liver development.…”
Section: Discussionmentioning
confidence: 99%
“…No. P0010, Beyotime Biotechnology, Shanghai, China) as previously described (Yan et al, 2020). 2.6 | RNA isolation, cDNA synthesis and qPCR…”
Section: Oil Red O Stainingmentioning
confidence: 99%
“…Protein concentration of each tissue or cell sample was determined as previously described (Yan et al, 2020). The protocol for immunoblot analysis was also previously described (Geng, Xia, Russo, et al, 2015).…”
Section: Protein Assay and Immunoblot Analysismentioning
confidence: 99%
“…Previous studies found that the expression level of circDock6 was downregulated in AML-12 cells, with the most signi cant increase in the mmu-let-7 g-5p expression level. Moreover, as the target of mmu-let-7 g-5p, IGF1R has been reported to be involved in metabolic homeostasis [13] and severe steatosis-associated injury [14].…”
Section: Introductionmentioning
confidence: 99%